High-energy bow tie multi-pass cells for nonlinear spectral broadening applications. (24th January 2022) - Heyl, Christoph M; Seidel, Marcus; Escoto, Esmerando; Schönberg, Arthur; Carlström, Stefanos; Arisholm, Gunnar; Lang, Tino; Hartl, Ingmar
Abstract: Multi-pass cells (MPCs) have emerged as very attractive tools for spectral broadening and post-compression applications. We discuss pulse energy limitations of standard MPCs considering basic geometrical scaling principles and introduce a novel energy scaling method using a MPC arranged in a bow tie geometry. Employing nonlinear pulse propagation simulations, we numerically demonstrate the compression of 125 mJ, 1 ps pulses to 50 fs using a compact 2 m long setup and outline routes to extend our approach into the Joule-regime.